Integrated vendor-buyer inventory model in a supply chain with variable lead time and setup cost reduction. (14th June 2019) - Uthayakumar, R.; Hemapriya, S.
The single vendor single-buyer integrated production inventory system has been an object of study for a long time but little is known about the effect of investing in reducing setup cost on the integrated inventory models with variable lead time and production lot size dependent lead time and transportation time. A mathematical model is derived to investigate the effects of setup cost reduction on the integrated inventory system by reducing the total cost system. A numerical example is included to illustrate the results of the model. Finally, graphical representation is presented to illustrate the model. The solution procedure is furnished to determine the optimal solution and the sensitivity analysis has been carried out to illustrate the behaviours of the proposed model.